Penetrating Liver Trauma Treated with a Multidisciplinary Approach in the Hybrid Emergency Room: All in One Room - Toshiki Nakazawa; Shokei Matsumoto; Natsuho Maekawa; Yudai Kumamoto; Masayuki Shimizu (Journal of Acute Care Surgery)
Early diagnosis and management of liver trauma with hemorrhagic shock occasionally necessitates a multidisciplinary approach, involving emergency services, radiology, and the operating room, to control significant hemorrhage. In recent years, the use of all-in-one resuscitation rooms in Japan, known as hybrid emergency rooms (ER), has been expanding for trauma care. We present a case of a 50-year-old man with penetrating liver trauma that was rapidly treated in the hybrid ER from diagnosis to definitive care from surgery to angioembolization without transferring the patient (240 minutes). The use of the hybrid ER system may improve survival rates in cases of penetrating torso trauma due to a shortened duration from patient arrival to diagnosis.